1996
DOI: 10.1177/155005949602700208
|View full text |Cite
|
Sign up to set email alerts
|

Diffuse Theta Activity and Spindle-Like Bursts during Coma after Cardiac Arrest

Abstract: An usual combination of diffuse theta activity with intermittent bursts of spindle-like activity, followed by 2-3 Hz rhythmic discharges and lasting about 7 seconds, was noted in a coma patient after cardiac arrest. We speculate that the theta pattern coma and spindle-like bursts originated in the pontine region, and that those bursts in turn triggered or recruited rhythmic slow-wave complexes similar to absence discharges.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1997
1997
2013
2013

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 21 publications
0
1
0
Order By: Relevance
“…Early studies reported slowing of the background frequencies as well as diffuse slow activity and increase in voltage of EEG frequencies in the theta and delta range in patients with metabolic abnormalities (Arjundas et al, 1965;Creutzfeldt and Meisch, 1963). These were dominant delta patterns, diffuse severe suppression, intermittent rhythmic delta activity (Accolla et al, 2011;Fariello et al, 1982;Hooshmand, 1983;Kameda et al, 1995;Nazarian et al, 1987;Woolridge et al, 2006), triphasic waves (TWs) (Bahamon-Dussan et al, 1989;Fisch and Klass, 1988;Kaplan and Birbeck, 2006;Karnaze and Bickford, 1984;Ogunyemi, 1996;Sundaram and Blume, 1987), diffuse unreactive alpha frequency patterns (Das et al, 2010;De Boer et al, 1989;Deleu and Ebinger, 1989;Dias and Scott, 1981;Guterman et al, 1981;Hrachovy, 1982;Iragui and McCutchen, 1983;Kaplan et al, 1999;Kuroiwa et al, 1981;Molofsky, 1982;Morioka et al, 1996;Pourmand and Markand, 1985;Synek and Glasgow, 1985;Young et al, 1994), and spindle-like sleep patterns (Bortone et al, 1996;Britt et al, 1980;Dadmehr et al, 1987;Das et al, 2010;Ganji et al, 1996;Kaplan et al, 2000;Lopez et al, 2002;Mouradian and Penovich, 1985;…”
Section: Eeg Approach To Diagnosismentioning
confidence: 99%
“…Early studies reported slowing of the background frequencies as well as diffuse slow activity and increase in voltage of EEG frequencies in the theta and delta range in patients with metabolic abnormalities (Arjundas et al, 1965;Creutzfeldt and Meisch, 1963). These were dominant delta patterns, diffuse severe suppression, intermittent rhythmic delta activity (Accolla et al, 2011;Fariello et al, 1982;Hooshmand, 1983;Kameda et al, 1995;Nazarian et al, 1987;Woolridge et al, 2006), triphasic waves (TWs) (Bahamon-Dussan et al, 1989;Fisch and Klass, 1988;Kaplan and Birbeck, 2006;Karnaze and Bickford, 1984;Ogunyemi, 1996;Sundaram and Blume, 1987), diffuse unreactive alpha frequency patterns (Das et al, 2010;De Boer et al, 1989;Deleu and Ebinger, 1989;Dias and Scott, 1981;Guterman et al, 1981;Hrachovy, 1982;Iragui and McCutchen, 1983;Kaplan et al, 1999;Kuroiwa et al, 1981;Molofsky, 1982;Morioka et al, 1996;Pourmand and Markand, 1985;Synek and Glasgow, 1985;Young et al, 1994), and spindle-like sleep patterns (Bortone et al, 1996;Britt et al, 1980;Dadmehr et al, 1987;Das et al, 2010;Ganji et al, 1996;Kaplan et al, 2000;Lopez et al, 2002;Mouradian and Penovich, 1985;…”
Section: Eeg Approach To Diagnosismentioning
confidence: 99%